Проект будівництва 7-ми поверхового житлового будинку на 56 квартир з вбудованим приміщенням кав’ярні в м. Кропивницький - Травкін, Данило Станіславович; Travkin, Danylo (ЦНТУ, 2024)
Запроектовано житловий будинок з вбудованим приміщенням кав’ярні, який має в плані розміри 48,000 х 12,000 м. Будівля семиповерхова, висота поверхів становить 2,8 м, загальна висота будівлі – 23,57 м. Проведено розрахунок збірної залізобетонної панелі перекриття і огляд сучасних методів розрахунку залізобетонних елементів. Здійснено розрахунок технологічної карти на мурування цегляних стін та розглянуто деякі аспекти охорони праці при проведенні земляних робіт. A residential building with built-in coffee shop space has been designed, which has the dimensions of 48,000 x 12,000 m in the plan. The building is seven-storey, the height of the floors is 2.8 m, the total height of the building is 23.57 m. The calculation of the prefabricated reinforced concrete floor panel and the review of modern methods of calculating reinforced concrete elements were also carried out. The calculation of the technological map for masonry of brick walls was carried out and some aspects of labor protection during earthworks were considered.
Construction project of a 7-story residential building with 56 apartments with built-in coffee shop premises in Kropyvnytskyi
Keywords: житловий будинок; перекриття; фундамент; residential building; ceiling; foundation